Validitas Dan Praktikalitas Modul Reaksi Redoks dan Sel Elektrokimia Berbasis Guided Discovery Learning untuk SMA - Yerimadesi, Yerimadesi; Bayharti, Bayharti; Oktavirayanti, Risa (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
Module based on guided discovery learning can be used as an alternative to improve studentâs activeness and understanding the concept. This research aims to develop redox reaction and electrochemical cell module based on guided discovery learning and reveals its validity and practicability. The type of this research is a development research using 4-D development model. The research instrument used was a questionnaire in the form of validity and practicality sheet. This module was validated by 3 UNP chemistry lecturers and 2 chemistry teachers of SMAN 10 Padang. Practicality test were conducted on 2 chemistry teachers and 32 twelfth grade students of SMAN 10 Padang. Data were analyzed by Cohenâs Kappa formula. The results of the validity test showed that the module has a very high validity category (k=0.83). Practicality test results by teachers and students showed that the module has high practicality category (k=0.79 and 0.80). Based on the results of this research, it can be concluded that the module developed was valid, practical.